Recent macroeconomic dynamics and agriculture in historical perspective - Orden, David (Cambridge University Press, 2010)
This article explores the similarities, differences, and implications from the 1970s-1980s experience for the macroeconomic dynamic that may arise from the 2008 price spike and subsequent recession. Role of monetary policy (deviations from Taylor rule) is assessed. This is an argument that has not been too prominent in public discourse about causes of the financial crisis or the policies undertaken to restore stability to financial markets and avoid an even deeper downturn than occurred. The “misery index” is compared across the past and recent macroeconomic events. Effects on agriculture of exchange rates are reviewed, effects dependent on currency values and interest rates that can change quickly and in unexpected ways.